Internal audit quality and disclosure on risk management and internal control - Zainal Abidin, Nor Hafizah (Conscientia Beam, 2021)
Disclosure and transparency are essential for informed decision-making. Timely reporting and accurate financial information including risk related information are key facets of investor protection and market confidence. This study examines the impact of internal audit quality on disclosure on risk management and internal control. The empirical evidence is gathered using data extracted from the annual report of 200 listed companies in 2017. Results indicate that higher internal audit quality significantly and positively enhances greater disclosure on risk management and internal control. Other characteristics such as firm size, firm liquidity, and audit firm size were further analyzed and found that those characteristics were not significantly related to the disclosure on risk management and internal control. Hence, this study provides empirical evidence on the likelihood of internal audit quality in facilitating the oversight duties of the audit committee and the board with regards to greater disclosure on risk management and internal control.